Mengelola Manajemen Logistik dengan Efektif di Universitas Negeri Semarang - Wisudani Rahmaningtyas; Ismiyati Ismiyati; Hengky Pramusinto (JSSH (Jurnal Sains Sosial dan Humaniora), 2017)
This research aims at analyzing the logistic management and examining the arising problems faced when managing the logistics at economics faculty of Semarang state university. Logistics is one essential administration that should be made by an organization. The logistic procedures consist of procurement, recording, storage, distribution, maintenance, and elimination. At present, the logistic activities at economics faculty are running quite well. However, based on the studies conducted by many researchers, the logistic impacts require further examination and analysis. The pre-research study based on interviews shows that no logistic staff handles the logistic management. For the time being, the logistic activities are handled by the public utility staffs. Besides, the Standardized Operational Procedures on logistic management are still unclear.This research uses a descriptive-qualitative approach. Data are obtained from informants in the forms of words, measures, and writings. Interview, observation, and documental analysis are techniques used to collect the data. Samples are taken with a purposive sampling technique and then data are analyzed using an interactive technique. Data validation is conducted using triangulation techniques and methodologies. The research results show that the logistic activities are not yet ideally running, such as poor conditioned inventory management of goods, uncontrolled stock opname; not maximally utilized forms as the controlling devices; limited warehouses for supply storage; unavailable warehouses for storage of the upcoming goods to eliminate, unscheduled goods inventory maintenance, and too long waiting period of elimination activities.